Highest Lesion Growth Rates in Patients With Hyperacute Stroke: When Time Is Brain Particularly Matters. Issue 1 (January 2019) - Broocks, Gabriel; Rajput, Furqan; Hanning, Uta; Faizy, Tobias Djamsched; Leischner, Hannes; Schön, Gerhard; Gellißen, Susanne; Sporns, Peter; Deb-Chatterji, Milani; Thomalla, Götz; Kemmling, Andre; Fiehler, Jens; et al.
Abstract : Background and Purpose—: The early growth of ischemic lesions has been described as being nonlinear, with lesion growth rates at their highest during the earliest period after stroke onset. We hypothesized that the time gap from imaging to revascularization results in higher lesion growth in patients with hyperacute presentation. Methods—: Fifty-one patients with ischemic stroke with initial multimodal computed tomography (CT), follow-up CT after 24 hours, and successful endovascular recanalization were included and separated into 2 groups according to their median time from symptom onset to imaging (eg, hyperacute versus acute). The difference in Alberta Stroke Program Early CT Score (ASPECTS) between initial CT and follow-up CT was assessed, as well as volumetric lesion growth from early ischemic core in admission perfusion CT and total lesion volume in follow-up CT. Results—: The median time from onset to imaging was 1.85 hours. There was no significant difference in admission ASPECTS (mean, 8.5 versus 8.2) or time from imaging to recanalization in both groups (median, 2.7 versus 2.4 hours; P =0.4). The mean (SD) lesion growth assessed by ASPECTS difference was 2.7 (2.3) in the hyperacute group and 1.6 (1.3) in the acute group ( P =0.03). The mean (SD) volumetric difference in the hyperacute group was 26.6 mL (43.2 mL) and 17.2 mL (26.3 mL; P =0.36) in the acute group, respectively. For every passing hour after onset, ASPECTS lesion growth was reduced by 0.4. Conclusions—: Patients in the hyperacute phase showed increased ASPECTS lesion growth from imaging to recanalization suggesting a particular benefit of faster recanalization times in this group of patients with stroke. Abstract : Supplemental Digital Content is available in the text.